Production of synthetic methanol from coco gas (high-pressure) - Dalisay, Divina E.; Dicioco, Leonora C.; Seneta, Alex S. (Diliman, Quezon City College of Engineering, 1975)
Capacity: 150 tons/day -- Land area: 5970 sq.m. -- Fixed capital investment: P 22,549,450 -- Operating cost at maximum production: P 55,783.78 per ton CH3OH -- Annual sales at maximum production: P 19,127,742 -- Pay-off time: 2.56 years -- Break even point: 33% of max. capacity
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Methanol fuel industry; Methanol as fuel